CHYTRIDS FROM LEAF LITTER IN PONDS OF VARANASI IV. GENUS RHIZOPHYDIUM - R. DAYAL, USHA KIRAN and (Indian Phytopathology, 2002)
During the survey of aquatic fungi from Varanasi, some interesting species of Rhizophydium have been isolated. This paper deals with three species of Rhizophydiu m, namely, R. dubium Kiran & Dayal sp. nov; R. subangulosum Rabenhorst; and R. globosum Rabenhorst. The former. is a new species, while the later two are new records from India.